Application of Management at the Pangkalan Masyhur Sub-District Office, Medan Johor District - Indah Mutiara Ayu (Penerbit Jurnal Indonesia, 2022)
The purpose of this study was to determine the application of management at the Pangkalan Masyhur sub-district office, Medan Johor district, which has been and discusses implementing managemement. The results showed that the implementation of work carried out at the Pangkalan Masyhur subdistrict office, Medan Johor subdistrict, was still carried out overlapping, many of the services expected by the community were late and tended to take a long time, because each employee waited for each other due to the lack of a typewriter/computer in making letters that society needs.